Relationship between study habits and academic achievement among health science students - Silverrajoo, Perimala; Hassan, Aminuddin (Human Resource Management Academic Research Society, 2018)
The objective of this study is to identify the relationship between study habits and academic achievements of Health Science Student’s in Masterskill University College of Health Sciences. This study also identifies the different study habit used by health science students and the academic achievement of the health science students. The overall health science students who participated in this survey were 150 (125 female and 25 male). Survey method was used in order to collect data through questionnaire. Factor analysis was carried out to group the variables under three different construct (UON, MOS, and Reading). Descriptive statistic was used to determine the different study habit practiced by the health science students and to identify the academic achievements of the health science students. Pearson Correlation analysis was used to view the relationship between underlining, outline summary and note taking (UON), method of study (MOS), and Reading method with the academic achievement of the health science students. The results of this study discovered that majority of the students are using the three different study habits mentioned in the questionnaire and their academic achievement shows that most of them are getting average level of CGPA. In measuring the relationship, the results shows that there is no significant relationship between UON and reading towards the academic achievements of the health science students. Whereby the relationship between MOS shows that there is a significant relationship to the academic achievement but it does not assist the towards the student’s academic performance as it shows a negative and weak relationship.